2021
DOI: 10.1039/d0py01645d
|View full text |Cite
|
Sign up to set email alerts
|

Design of an n-type low glass transition temperature radical polymer

Abstract: We document the design, synthesis, and characterization of the first low glass transition temperature, n-type (i.e., preferentially-reduced) radical polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…Post-polymerization modification of existing polymer motifs (e.g., by grafting to a polymer backbone with a radical-containing side chain) through the attachment of open-shell units (or precursors) provides an additional alternative in the syntheses of advanced polymer architectures. For instance, coupling and click reactions have been employed, and various pre-synthesized polymer structures have been combined to yield non-conjugated radical polymers, which highlights the robust nature of this approach. For example, the synthesis of poly­[2,6-di- tert -butyl-4-((3,5-di- tert -butyl-4-(λ 1 -oxidaneyl)­phenyl)­(4-((3-(methoxydimethylsilyl)­propoxy)­methyl)­phenyl)­methylene)­cyclohexa-2,5-dien-1-one] (PGMS) was carried out through hydrosilylation of poly­(methylhydrosiloxane) with 4-allyl-galvinoxyl-H catalyzed by a platinum complex, followed by oxidation to produce the radical polymer . The post-modification method, in general, follows a statistical incorporation, as the radical content can be quantitatively measured.…”
Section: Synthesis Of Open-shell Macromoleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-polymerization modification of existing polymer motifs (e.g., by grafting to a polymer backbone with a radical-containing side chain) through the attachment of open-shell units (or precursors) provides an additional alternative in the syntheses of advanced polymer architectures. For instance, coupling and click reactions have been employed, and various pre-synthesized polymer structures have been combined to yield non-conjugated radical polymers, which highlights the robust nature of this approach. For example, the synthesis of poly­[2,6-di- tert -butyl-4-((3,5-di- tert -butyl-4-(λ 1 -oxidaneyl)­phenyl)­(4-((3-(methoxydimethylsilyl)­propoxy)­methyl)­phenyl)­methylene)­cyclohexa-2,5-dien-1-one] (PGMS) was carried out through hydrosilylation of poly­(methylhydrosiloxane) with 4-allyl-galvinoxyl-H catalyzed by a platinum complex, followed by oxidation to produce the radical polymer . The post-modification method, in general, follows a statistical incorporation, as the radical content can be quantitatively measured.…”
Section: Synthesis Of Open-shell Macromoleculesmentioning
confidence: 99%
“…Quantifying the effects of charge carrier densities and carrier mobility on the solid-state conductivity of non-conjugated radical polymers has proven challenging. By comparing the Kuhn length and the polymer contour length, Martin et al concluded that an increased radical content will lead to a more rigid PTMA polymer and a closer intermolecular radical proximity. , Computational simulations of PGMS, an n-type radical polymer based on the galvinoxyl radical, also suggested that the intrachain coupling between radicals can saturate at concentrations as low as 50% when the radicals have a strong propensity to aggregate, while still requiring high loadings for effective interchain transport . Thus, while it is difficult to separate the distinct factors that accompany an increased charge carrier density, the evidence suggests that higher radical loadings are essential for obtaining significant charge transport.…”
Section: Charge and Mass Transport In Open-shell Macromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical polymers (i.e., macromolecules with nonconjugated backbones and stable open-shell moieties present on their pendant sites) are an emerging class of organic electronic materials with myriad potential applications in rechargeable batteries, electrochemical devices, and solid-state electronics. Because they are nonconjugated, their charge transport and redox-activity are localized to the pendant groups while the polymeric backbone dominates the thermal and mechanical properties of radical polymers. This modular design enables a potentially enormous range of open-shell groups to be combined with varying backbones to tune both the electronic and mechanical properties of these materials in a decoupled, and potentially powerful, manner.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] More recently, many efforts have evaluated the solid-state electronic conductivity of radical polymers, such as poly (2,2,6,6-tetramethylpiperidinyloxy methacrylate), 18-21 poly(2,3-bis(2 0 ,2 0 ,6 0 ,6 0 -tetramethylpiperidinyl-N-oxyl-4 0oxycarbonyl)-5-norbornene), 22 and poly(galvinoxyl methyl siloxane). 23 Furthermore, the radical polymer that has the highest reported solid-state conductivity of $20 S m À1 is poly (4-glycidyloxy-2,2,6,6-tetramethylpiperidine-1-oxyl) (PTEO), a low-glass transition temperature (T g ) radical polymer.…”
Section: Introductionmentioning
confidence: 99%